Husband's Obligation to Provide Financial Maintenance for Career Wives in the Modern Context: Perspectives of Dayah Scholars in Pidie Jaya - Munawiah Abdullah; Januddin Januddin; Nurlinda Yani (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
This study aims to analyze a husband's obligation to provide financial maintenance (nafaqah) to a career wife from the perspective of Dayah Ulama (traditional Islamic scholars) in Pidie Jaya Regency. Amidst social transformation and digitalization, the phenomenon of wives serving as the primary breadwinners has become increasingly prevalent across several sub-districts, namely Meureudu, Meurah Dua, Bandar Baru, and Trienggadeng. Sociological realities indicate a degradation of marital responsibility among husbands, who tend to be negligent and spend excessive time in informal spaces such as coffee shops, thereby shifting both domestic and financial burdens onto the wives. Data gathered through in-depth interviews with key Dayah Ulama figures demonstrate that providing financial maintenance remains the absolute responsibility of the husband as an individual obligation (fardhu 'ayn), irrespective of the wife's economic status. A wife’s status as a career woman does not annul her right to maintenance, as it constitutes a legal consequence ('iwadh) of the marriage contract. The Dayah Ulama perceive the wife's financial contribution not as a mandatory obligation, but as a form of voluntary assistance (tabarru') that holds spiritual merit ('ibadah). Conversely, pursuing a career does not grant an automatic dispensation for a wife to neglect her domestic duties and childcare. The scholars emphasize the urgency of revitalizing the concepts of mu'asharah bil ma'ruf (kind companionship) and ta'awun (mutual assistance) within the household. As a theological solution, this study proposes a relational model wherein the husband maintains his role as the primary protector, while the wife functions as an honorable domestic manager. This model serves to preserve family stability in the modern era in accordance with the principles of Maqasid al-Shari'ah.